PENGEMBANGAN PRODUK UMKM MAJU MAPAN DENGAN STRATEGI MODERNISASI DI ERA TEKNOLOGI 5.0 - Andri Wahyu Utomo; Tina Fitri Andriyanti, Fitri Nurharyati, Wisnu Juania Indriani, Dewi Fortuna (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
The lack of knowledge regarding business legality, provisions for packing and product labels, as well as marketing which is only in a small scope are the problems faced by MSME (Micro, Small and Medium Enterprises) actors in Kenongorejo Village. The implementation of this community service is one of the efforts to develop the business of MSME players in Kenongorejo Village to increase the selling power of production through business legality, improvement of appropriate packaging and labels, and improvement of product marketing. The final objectives to be achieved from this activity are 1) business legality of the products produced, 2) improvement of packaging and labels, 3) improvement of marketing management through increased photography skills. This form of community service activity is carried out through outreach and assistance to solve problems being faced by partners. Business permits that will be carried out include registration of NIB, PIRT, and product halal guarantee certification. In addition, training was also carried out in fulfilling product packaging and labeling requirements, as well as photography skills for product marketing. It is hoped that with the implementation of this community service activity, MSMEs in Kenongorejo Village can develop their business and market their products to a wider market so that their selling power will increase according to the technology that has developed